Genome-Wide Profiling of Prognostic Alternative Splicing Pattern in Pancreatic Cancer - Yu, Min; Hong, Weifeng; Ruan, Shiye; Guan, Renguo; Tu, Lei; Huang, Bowen; Hou, Baohua; Jian, Zhixiang; Ma, Liheng; Jin, Haosheng (Frontiers in Oncology, 2019)
Alternative splicing (AS) has a critical role in tumor progression and prognosis. Our study aimed to investigate pancreatic cancer-specific AS events using RNA-seq data, gaining systematic insights into potential prognostic predictors. We downloaded 10623 genes with 45313 pancreatic cancer-specific AS events from the Cancer Genome Atlas (TCGA) and SpliceSeq database. Cox univariate analyses of overall survival suggested there was a remarkable association between 6711 AS events and overall survival in pancreatic cancer patients (P<0.05). The area under the curves of the receiver operator characteristic curves（ROC）of risk score was 0.89 for final prognostic predictor. Results indicated that AS events of DAZAP1, RBM4, ESRP1, QKI, and SF1 were significantly associated with overall survival. The results of FunRich showed that transcription factors KLF7, GABPA, and SP1 were the most highly related to survival-associated AS genes. Furthermore, using DriverDBv2, we identified 13 driver genes associated with survival-associated AS events, including TP53 and CDC27. Thus, we concluded that the aberrant AS patterns in pancreatic cancer patients might serve as prognostic predictors.